SARS-CoV-2 (COVID-19) and Chronic Myeloid Leukemia (CML): a case report and review of ABL kinase involvement in viral infection - Elisabetta Abruzzese; luigia luciano; Francesco D'Agostino; Malgorzata Monika Trawinska; Fabrizio Pane; Paolo de Fabritiis (Mediterranean Journal of Hematology and Infectious Diseases)
no abstract available